2017
DOI: 10.21833/ijaas.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

A study of volatility behaviour of S&P BSE BANKEX return in India: A pragmatic approach using GARCH model

Abstract: The purpose of this study is to know that how the National and International market, namely (S&P BSE SENSEX) (NASDAQ) (SSE) (FTSE) can influence the volatility of (S&P BSE BANKEX) return in India and the factors affecting the volatility for the same. However, the previous studies mostly considered the volatility of stock in the Indian capital market. But the present study mainly focuses on the Bankex return volatility. Here the researcher identified and estimated the mean and variance components of the daily B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As males dominate the board members, the risk-taking incentives of the corporation can be influenced by the interests of the controller group in which female directors may conduct themselves differently (Bianco, Ciavarella, & Signoretti, 2015) seeing that women also bring different professional capabilities and assessment. Female directors with more risk-averse behaviors possibly make the decision-making process longer (Berger et al, 2014;Khan & Javed, 2017).…”
Section: Gender Diversitymentioning
confidence: 99%
“…As males dominate the board members, the risk-taking incentives of the corporation can be influenced by the interests of the controller group in which female directors may conduct themselves differently (Bianco, Ciavarella, & Signoretti, 2015) seeing that women also bring different professional capabilities and assessment. Female directors with more risk-averse behaviors possibly make the decision-making process longer (Berger et al, 2014;Khan & Javed, 2017).…”
Section: Gender Diversitymentioning
confidence: 99%
“…The study used regression analysis and found that crude oil prices, inflation, and exchange rates had a significant brunt on the S&P BSE Bankex returns. Khan and Javed (2017) used the GARCH model to examine the impulsiveness and volatility behavior of the S&P BSE Bankex returns. According to the study, the GARCH model successfully reflects the S&P BSE Bankex returns' volatility trend patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khan and Javed (2017) used the GARCH model to examine the impulsiveness and volatility behavior of the S&P BSE Bankex returns. According to the study, the GARCH model successfully reflects the S&P BSE Bankex returns' volatility trend patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study on volatility behaviour of S&P BSE BANKEX return in India carried out by Khan and Javed (2017) and Javed (2018) the results indicate that S&P BSE Bankex return volatility not only shows ARCH AND GARCH effect but also shows significant influenced by National market (SENSEX) return volatility and also influence or transmit outside shock in the International market return namely the Nasdaq and Shanghai stock Exchange.…”
Section: Introductionmentioning
confidence: 99%